2021
DOI: 10.1186/s12951-021-00984-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of the electrokinetic charge of neurotrophis-based nanocarriers: protein distribution, toxicity, and oxidative stress in in vitro setting

Abstract: Background The rational chemical design of nanoparticles can be readily controlled and optimized by quantitatively studying protein adsorption at variously charged polymer carriers, determining their fate in biological fluids. We manufactured brain-derived neurotrophic factor (BDNF) -based electrostatic nanocomplexes with a different type of dendrimer core (anionic or cationic), encapsulated or not in polyethylene glycol (PEG), and studied their physicochemical properties and behavior in a biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…According to our previous work 11 , BDNF molecule has a slightly positive electrokinetic charge under physiological conditions, which explains a signi cant increase of BDNF adsorption on the negatively charged HP layer. Decreasing the zeta potential of the PDADMAC-terminated multilayer (see Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…According to our previous work 11 , BDNF molecule has a slightly positive electrokinetic charge under physiological conditions, which explains a signi cant increase of BDNF adsorption on the negatively charged HP layer. Decreasing the zeta potential of the PDADMAC-terminated multilayer (see Fig.…”
Section: Discussionmentioning
confidence: 78%
“…It should be underlined that BDNF's role is rather complex. For instance, the literature data suggests that high BDNF levels might be associated with malignant disease progression and cancer cell survival 9,10 , and our previous studies showed that BDNF improves the recovery of damaged neuroblastoma cells 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in vivo studies of the embryonic zebrafish model have shown that the surface charge properties of dendrimers is a more important factor in the cytotoxicity of dendrimers than either generation or size [71]. When dendrimers were applied as nanocarriers, positively charged dendrimer cores exhibited significant cytotoxicity and severe phenotypic changes, compared with negatively charged dendrimer cores [72].…”
Section: Chargementioning
confidence: 99%
“…25,26 Positively charged particles were also reported to be readily taken up into DCs due to the ionic attraction with the negatively charged cell membrane, which initiates efficient binding and facilitates particle internalization. 27,28 However, the effect of the particle topological structure on antigentargeted delivery has remained unexplored. Thus, understanding how the topological structure influences immune responses can greatly aid in the rational design of better vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Because the uptake of antigen by DCs plays a critical role in the induction of innate and adaptive immunity, the delivery systems that not only can protect the antigens from degradation , but also can facilitate the interaction with DCs would be a promising strategy for vaccine development. The physicochemical characteristics of particles, such as the size, surface properties, rigidity, and shape, all significantly influence the in vivo trafficking and cellular internalization. It has been reported that particles with an intermediate size (10–100 nm in diameter) can both efficiently drain to regional draining lymph nodes and become retained there to increase the chance of antigen uptake and presentation by APCs. , Positively charged particles were also reported to be readily taken up into DCs due to the ionic attraction with the negatively charged cell membrane, which initiates efficient binding and facilitates particle internalization. , However, the effect of the particle topological structure on antigen-targeted delivery has remained unexplored. Thus, understanding how the topological structure influences immune responses can greatly aid in the rational design of better vaccines.…”
Section: Introductionmentioning
confidence: 99%